Eksistensi Diri Pengguna Photo Booth Di Kabupaten Aceh Barat - Renzi Anita; Rahma Hidayati; Reni Juliani (Universitas Teuku Umar, 2019)
Photo Booth has become a contemporary phenomenon among the public, especially during weddings. So from that the West Aceh Society made the wedding event photo booth as the medium of his existence. The purpose of this study was to find out how wedding event photo booths were used for most of the West Aceh community to show their existence. This study uses a qualitative descriptive approach to collecting field data and observations. The results showed that the event wedding photo booth users used photo booth as a medium of self-existence with their various views on the photo booth, namely photo booth seemed luxurious, unique, beautiful, and of course present. The concept of looking glass that forms a mirror of the user of a photo booth on a positive self-concept, that a photo booth user claims to be proud of himself towards the judgment of others if he uses a photo booth. Besides that, the photo booth is a photo booth besides wedding. they shared the moment when he took a photo in the photo booth area to social media. Based on this, photo booth users want to build their existence to appear to have high social status among other communities. Keywords: Photo booth, Event Wedding, Existence